RITUAL BELA DIRI KUTAU DALAM MASYARAKAT DESA SURO, KABUPATEN MUSI RAWAS - Lidiantari, Aulini; Muliati, Roza; Nursyirwan, Nursyirwan; Minawati, Rosta (UI Scholars Hub, 2024)
This paper discusses the Kutau martial arts ritual practiced by the people of Suro Village, Muara Beliti District, Musi Rawas Regency, South Sumatra Province. Kutau is one of the ancestral heritages consisting of a set of rituals. Kutau takes the form of traditional martial arts that has been developed by the Suro Village community. Applying the qualitative approach, this study aimed to systematically document all forms of rituals in Kutau and its functions within the Suro community. Data were collected through observation, interviews, and documentation, which were then analyzed using Victor Turner’s ritual approach and Talcot Parsons’ function approach. Results show that Kutau is a medium of communication between the community and their ancestors to pass down the Kutau knowledge, which is closely related to Suro people’s belief system. Kutau still prevails thanks to the latency function of the Kutau community, so that the whole system is able to survive and adapt to the current society.